EVALUACIÓN DEL COMPORTAMIENTO CARDÍACO MEDIANTE UNA METODOLOGÍA DIAGNÓSTICA BASADA EN SISTEMAS DINÁMICOS EN 16 HORAS (2018)
Background: With concepts derived from dynamical systems theory and fractal geometry, it has been possible to characterize the behavior of the cardiac dynamics, giving objective results and establishing dis tinctions between states of normality and disease Objective: To apply an exponential mathematical law of cardiac dynamics, inscribed in the context of dynamical systems and fractal geometry, to demonstrate its diagnostic utility in the context of a reduction in the evaluation time, originally of 21 hours. Materials and methods: There were used 200 Holters and continuous electrocardiographic records, between normal and with different cardiac alterations. A sequence of heart rates was simulated in 16 and 21 hours, with which the attractor of each dynamic was constructed. There were also calculated the fractal dimension and the occupation of the attractors in the fractal space. The physical-mathematical diagnosis was established at 16 and 21 hours, and the statistical validation was performed. Results: Values obtained in the Kp grid were between 44 y 198 for pathological states, and between 221 and 377 for normal states in 16 hours. The sensitivity and specificity was 100% and the Kappa coefficient was 1. Conclusion: It was possible to differentiate adequately normal states of pathological by means of the exponential law applied in registers of 16 hours. © 2018, Ediciones Medicas del Sur S.R.L.. All rights reserved.